Prevalence of Seizure Disorders in Children with Communication Disorders- A Preliminary Study - Sangeetha Mahesh; Geetha Y.V. (Journal of All India Institute of Speech and Hearing, 1970)
The word “Epilepsy” is derived from a Greek word which means to seize. Jackson (1931) defines, “Epilepsy as sudden, excessive, rapid and local discharge of gray matter”. Epileptic seizures are usually brief, lasting from second to minutes, and they are marked by the sudden appearance of behavioral manifestation that may be purely motor or that may affect other brain functions. It is known to co-exist or develop as a range of childhood conditions in which there is Central Nervous System (CNS) involvement. Seizures occur more frequently in children with communication disorders than in the general population. However, prevalence of epileptic seizures in children with communication disorders is not clearly understood. There is an urgent need for studies regarding prevalence of epileptic seizures in communication disorders. Hence the presentstudy was planned. The subjects considered in the study included children below the age of 12 years, who had visited AIISH with the complaint of speech, language and hearing problems over a period of two years (Jan 2007- Dec 2008). Case files of these children were reviewed for the presence or absence of seizures and type of associated communication disorders. Results revealed that out of 6,101 children with communication disorders, who were registered during the period, 730 children had positive history of seizures. A total percentage of communication disorder having positive history of seizures was 11.96% whereas in general population it is about 3-5%. The gender wise distribution revealed that boys had 74.1% (541/730) and girls had 25.9% (189/730) history of seizures. It was noted that epileptic seizures are one of the most common neurological disorders occurring in children with communication disorders. The prevalence figure varied widely across the clinical population. These findings suggest measures to control seizures in the subgroups of communication disorders as the presence of seizures is a deterrent to physical and mental progress.